Context and Management Strategies for the Dental Care of Tourette’s Children - Ahmed Abulwefa; Wageh Twati; Salah Kurdi (Khalij-Libya Journal of Dental and Medical Research, 2025)
Tourette syndrome (TS) is a neurodevelopmental disorder that typically emerges in children between 6-8 years old. The syndrome was identified by Gilles de la Tourette in France in 1885. The syndrome refers to the combination of motor and vocal tics. TS affects individuals from all social, racial, and ethnic groups, with a prevalence of approximately 1% among school-age children. Recurrent and involuntary, non-rhythmic, sudden motor tics are the main symptom. Tics are more likely to affect boys than girls by a ratio of 1.5–4:1. It is classified as a multifaceted neurodevelopmental and neuropsychiatric disorder, believed to result from a complex interaction between social, environmental, and multiple genetic risk factors. This interaction highlights the complexity of management and points to the need for comprehensive therapeutic approaches. Maintaining routine daily oral hygiene is challenging due to this tic that affects the head, neck, shoulders, and arms, which hinders the oral hygiene process and increases the difficulty of providing dental treatment. Tourette's children suffer from consequences including tooth decay, gingival disease, grinding teeth, malocclusion, and trauma. These children often face difficulty accessing dental treatment due to multiple barriers, especially in Libya, where these patients face significant problems seeing a dentist. We zoomed in on the Tourette’s children and focused on their oral health. As far as we know, this is the first article published in Libya regarding this syndrome. We share with you updated and distinctive preparatory steps to participate in supporting this group of children to get rid of pain and inflammation This perspective article provides dental practitioners and oral health care professionals with essential insights into the context and management strategies for dealing effectively with children and adolescents affected by TS. When we have the opportunity to save a child from pain and suffering, effective symptom management is always easier than treating complications.